Effect of Abutilon indicum in thyroxine-induced hyperthyroidism in rat (Bangladesh Journal of Pharmacology, 2021)
The study was designed to investigate the antithyroid activity of the crude methanolic (70%) extract of aerial parts of Abutilon indicum in male albino rats. The extract was prepared and analyzed for the presence of phytochemical constituents through preliminary chemical analysis, antioxidant assay and GC-MS. The in vivo antithyroid activities in thyroxine-induced hyperthyroidism were studied. Phytochemical analysis showed the presence of alkaloids, flavonoids and phenols, also verified by the data obtained from GC-MS. Thyroxine increased the levels of triiodothyronine (4.9 ± 0.1 ng/mL) and total thyroxine (9.4 ± 0.2 μg/dL); while, A. indicum at the doses of 300 and 500 mg/kg, showed significant decrease in the elevated levels of triiodothyronine (3.0 ± 0.1 and 2.6 ± 0.2 ng/mL) and thyroxine (7.7 ± 0.2 and 7.1 ± 0.2 μg/dL), respectively. Histopathological studies showed the restoration of filled follicular colloids in extract-treated animals. The results show that A. indicum exhibits dose-dependent antithyroid effects.